2006
DOI: 10.1111/j.1471-0528.2006.01020.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of maternal methadone use on the fetal heart pattern: a computerised CTG analysis

Abstract: Using a computerised analysis, the cardiotocograph (CTG) from women who use methadone (n = 25) when compared with women who do not use methadone (n = 25) showed a significant reduction in the fetal heart baseline rate, with a significant reduction in number of accelerations and episodes of high variation. The short-term variation, number of decelerations and episodes of low variation were not different between the two groups. The time taken to meet the standardised criteria was not different, and it is possibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…Our data suggest that the effect of opioid intake needs to be taken into consideration when interpreting FHR in opioid‐dependent mothers at first‐trimester screening. While the effects of maternal opioid dependency on near‐term fetuses and neonates have been well described [15–20], we are the first to report on a decreased FHR in opioid‐dependent mothers in the first trimester of pregnancy. However, the observed difference between both groups was relatively small compared to what has been reported in late gestation.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Our data suggest that the effect of opioid intake needs to be taken into consideration when interpreting FHR in opioid‐dependent mothers at first‐trimester screening. While the effects of maternal opioid dependency on near‐term fetuses and neonates have been well described [15–20], we are the first to report on a decreased FHR in opioid‐dependent mothers in the first trimester of pregnancy. However, the observed difference between both groups was relatively small compared to what has been reported in late gestation.…”
Section: Discussionmentioning
confidence: 76%
“…In opioid‐dependent mothers, FHR, number of accelerations and episodes of high variability are reduced significantly in the third trimester of pregnancy [15]. A number of studies have found less reactivity in non‐stress testing in methadone‐exposed fetuses when compared with controls [16–19].…”
Section: Introductionmentioning
confidence: 99%
“…Animal literature has shown that prenatal methadone exposure predicates a disruption to neural maturation in exposed fetuses [21,22], and there is evidence of similar disruption in human neurodevelopment. When compared to non-exposed fetuses, methadone-exposed fetuses have reduced baseline heart rate, proportion of accelerations [17, 20], and heart rate variability [20]. At times of maternal peak methadone levels, methadone-exposed fetuses have less motor activity [24, 10] slower and less variable heart rates, and attenuated integration between fetal heart rate and fetal movement [10] compared to the same fetuses at times of trough maternal methadone levels.…”
Section: Inroductionmentioning
confidence: 99%
“…A dose-dependent effect of cocaine on respiratory sinus arrhythmia has been reported (Scheutze & Eiden, 2006). Prenatal methadone exposure is associated with disruption to autonomic functioning in the developing fetus expressed as decreased fetal heart rate variability (Ramirez-Cacho, et al, 2006; Navaneethakrishnan et al, 2006; Jansson et al, 2005) and with disruption to maternal autonomic functioning and subsequent NAS expression in the infant (Jansson et al, 2007). …”
Section: Introductionmentioning
confidence: 99%